Single cell viral tagging of Faecalibacterium prausnitzii reveals rare bacteriophages omitted by other techniques - Danielle E. Campbell; Xiaofen Wu; Lindsey R. Hall; Dylan Lawrence; Jerome M. Molleston; Lawrence A. Schriefer; Lindsay Droit; James S. Weagley; Benjamin S. Olson; Joanna Rimmer; Miles Parkes; Scott A. Handley; et al. (Gut Microbes)
The associations of the gut microbiome and virome with human health and disease are increasingly numerous and clear. The mechanistic roles of bacteriophages (phages) in the microbiome, however, are especially unclear, as their cultivation is exceedingly difficult and their diversity so immense. We use viral tagging (VT), a technique wherein fluorescently stained uncultivated viruses are allowed to adsorb to host cells and then host cells are singly sorted. This method identifies interacting phage-bacteria pairs to better sample and characterize the phages in human stool samples from healthy and inflammatory bowel disease (IBD)-affected patients. First, we apply VT to uncultivated bacteria from a healthy human sample, demonstrating far-reaching ability to observe diverse bacteria and phages alike. We also use VT with a cultured Faecalibacterium prausnitzii isolate, a bacterial host of interest due to its anti-inflammatory effects and strong negative correlation with IBD. Comparing VT with virome sequencing and phage identification from single amplified genomes shows that it is a practical technique for phage discovery, especially when it is used to focus on individual bacterial cultivars for which genomes have been sequenced. VT can detect phages so rare as to be undetectable in standard virome sequencing, which is biased toward the most abundant phage species even at high sequencing depth. Remarkably, VT also identified novel prophage integration events in F. prausnitzii, demonstrating that VT interactions can extend beyond the level of surface attachment and constitute active infection events. In total, VT identified at least 328 unique and highly diverse phage-host pairs, almost all of which are entirely uncharacterized, and several phages that are differentially abundant in IBD patients compared to healthy controls. Taken together, we show that VT is an extremely powerful tool to move beyond the cultivation and abundance biases inherent to current techniques and suggest that the phage-host pairs identified by VT here are crucial first step to enable future mechanistic studies of phage-bacteria-human interactions.